2012
DOI: 10.1016/s2255-4971(15)30105-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Results From Arthroscopic Surgical Treatment for Traumatic Anterior Shoulder Instability Using Suturing of the Lesion at the Opened Margin of the Glenoid Cavity

Abstract: Objective: To evaluate the clinical results from patients with traumatic anterior shoulder instability that was treated surgically through arthroscopic viewing, using bioabsorbable anchors and a technique for remove the cartilage of the anterior glenoid rim for repairing a Bankart lesion. Method: Between March 2006 and October 2008, 27 shoulders in 27 patients with a diagnosis of traumatic anterior shoulder instability were operated. The patients’ mean age was 28 years and they had had between two and 25 previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 24 publications
(24 reference statements)
1
8
0
7
Order By: Relevance
“…Those authors did not include in the analysis cases that presented recurrence. 9 In the present study, presence of shoulder pain complaints was observed in 30% of the sample. Presence of pain does not appear to be related to treatment success or failure.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…Those authors did not include in the analysis cases that presented recurrence. 9 In the present study, presence of shoulder pain complaints was observed in 30% of the sample. Presence of pain does not appear to be related to treatment success or failure.…”
Section: Discussionsupporting
confidence: 52%
“… 19 The sample recurrence rate was 10%, but most athletes presented pain complaints even without recurrence, especially when doing activities that required excessive effort shoulder. 19 Miyazaki et al 9 observed a rate of 8% for persistence of postoperative pain without a plausible explanation for patients with good result at the end of treatment. Those authors did not include in the analysis cases that presented recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of glenohumeral instability is approximately 1.7 injuries for each 1000 people in the American and European population, and a traumatic cause is responsible for the vast majority of cases. 20,21…”
mentioning
confidence: 99%